Valve-sparing aortic root and aortic arch replacement in a 5-year-old boy with Loeys–Dietz syndrome. (3rd January 2019) - Ajmi, Houda; Arifa, Nadia; Boughzela, Essia; Ben Mime, Lotfi
Abstract: In this study, we describe the case of a 5-year-old boy who presumably presented with Loeys–Dietz syndrome. A huge aneurysm of the ascending aorta and the aortic arch extended beyond the left subclavian artery and was accompanied by a slight narrowing of the aortic isthmus.